Rivaroxaban Once-Daily vs. Dose-Adjusted Vitamin K Antagonist on Biomarkers in Acute Decompensated Heart Failure and Atrial Fibrillation (ROAD HF-AF): Rationale and Design of an Investigator-Initiated Multicenter Randomized Prospective Open-Labeled Pilot Clinical Study - Cho, Iksung; Oh, Jaewon; Kim, In-Cheol; Chung, Hyemoon; Lee, Jung-Hee; Kim, Hyue Mee; Byun, Young Sup; Yoo, Byung-Su; Choi, Eui-Young; Chung, Wook-Jin; Pyun, Wook Bum; Kang, Seok-Min (Frontiers in Cardiovascular Medicine, 2022)
Background: Clinical trials of non-vitamin K antagonist oral anticoagulants (NOACs) in patients with chronic heart failure and atrial fibrillation (AF) have demonstrated reduced risks of stroke and bleeding compared with vitamin K antagonists (VKAs). Here, we aim to assess the clinical efficacy and safety of rivaroxaban, a NOAC, compared with warfarin, a VKA, and the effects of rivaroxaban on cardiovascular biomarkers in patients with acute decompensated heart failure (ADHF) with reduced ejection fraction (≤40%) and AF. Methods: Rivaroxaban Once-daily vs. dose-adjusted vitamin K antagonist on biomarkers in Acute Decompensated Heart Failure and Atrial Fibrillation (ROAD HF-AF) is a randomized, open-labeled, controlled, prospective, multicenter pilot study designed to assess cardiovascular biomarkers and the safety of rivaroxaban (20 or 15 mg in patients with creatinine clearance 30–49 mL/min per day) compared with VKA (target international normalized range: 2–3) in 150 patients hospitalized with ADHF and AF. The primary endpoint is the change in circulating high-sensitivity cardiac troponin (hsTn) during hospitalization. The secondary endpoints are bleeding, hospital stay duration, in-hospital mortality, and changes in cardiovascular, renal, and thrombosis biomarkers. Patients will be followed for 180 days. Conclusion: We hypothesize that rivaroxaban will reduce myocardial injury and hemodynamic stress, as reflected by the biomarker status, within 72 h in patients with ADHF and AF, compared with VKA. We hope to facilitate future biomarker-based, large-scale outcome trials using NOACs in patients with ADHF and AF, based on the results of this multicenter, randomized, controlled study.